2017
DOI: 10.1007/s10995-016-2241-4
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Birthplace is Associated with Low Birth Weight Within Racial/Ethnic Groups

Abstract: Introduction While disparities in low birth weight (LBW) incidence by racial/ethnic group are well known, differences in LBW incidence by maternal birthplace within racial/ethnic groups, and particularly, differences after adjustment for pregnancy complications, are less clear. Methods We conducted a population-based study of LBW using 113,760 singleton, live birth records from King County, Washington (2008–2012), a region in the Pacific Northwest with a large immigrant population. Study participants were As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Several studies acknowledged that disaggregating Pacific Islander ethnicities into their individual subgroups would have strengthened their analyses, but in many cases, they cited small sample size as a barrier to doing so [ 35 , 43 , 50 , 58 , 67 , 69 ]. Despite the fact that 0.4% of the U.S. population identified as Pacific Islander in the 2020 census [ 82 ], and that this group grew by 35% from 2000 to 2010 [ 16 ] (more than three times faster than the rate of the overall U.S. population) and another 28% between 2010 and 2020 [ 82 ], representation – particularly in studies using national-level data – fell short of what may have been expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies acknowledged that disaggregating Pacific Islander ethnicities into their individual subgroups would have strengthened their analyses, but in many cases, they cited small sample size as a barrier to doing so [ 35 , 43 , 50 , 58 , 67 , 69 ]. Despite the fact that 0.4% of the U.S. population identified as Pacific Islander in the 2020 census [ 82 ], and that this group grew by 35% from 2000 to 2010 [ 16 ] (more than three times faster than the rate of the overall U.S. population) and another 28% between 2010 and 2020 [ 82 ], representation – particularly in studies using national-level data – fell short of what may have been expected.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, several studies of pregnancy hypertension and diabetes had to be excluded for not distinguishing between pre-existing and pregnancy-induced dysfunction. [ 20 , 88 ] While the main goal of this paper was not to compare Pacific Islanders’ risk for poor pregnancy/perinatal outcomes to those of other groups, but rather to identify gaps in the research, it should be noted that the majority of studies found that Pacific Islanders had higher prevalence, risk, or odds of having adverse outcomes compared to their white counterparts [ 27 32 , 34 – 39 , 41 49 , 51 , 52 , 58 – 65 , 67 – 73 ]. The underlying cause of these disparities needs further research but may be due to lack of healthcare access, discrimination, or other social determinants as have been reported among other U.S. minority/immigrant populations [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, this study is based on a large population with comprehensive demographic and health care information, allowing an investigation of a number of adverse perinatal outcomes with appropriate adjustment for potential confounding factors. Second, our study has a large sample size of Asian women, enabling a robust comparison between Caucasians and Asians with greater than at least 90% power to detect the difference for each perinatal outcome with a two-tailed alpha (type 1 error) of 5%, where previous studies had smaller samples of Asians [ 1 , 7 , 18 , 54 , 55 ]. Third, universal access to quality maternity care helped to isolate maternal factors from health care factors.…”
Section: Discussionmentioning
confidence: 99%
“…Marshallese in the United States experience significant health disparities and report a high prevalence of diabetes, heart disease, and obesity (Hawley & McGarvey, 2015;Look et al, 2013;Mau et al, 2009;McElfish et al, 2017aMcElfish et al, , 2017bOkihiro & Harrigan, 2005;Schiller et al, 2012;Tung, 2012;US Department of Health & Human Services Office of Minority Health, 2015). Furthermore, Marshallese mothers are disproportionately likely to have poor maternal health outcomes compared to other racial and/or ethnic groups (Centers for Disease Control & Prevention, 2011;Chang et al, 2010Chang et al, , 2015Lavery et al, 2017;Nembhard et al, 2019aNembhard et al, , 2019bRao et al, 2006;Silva et al, 2006;Tsitas et al, 2015;Wartko et al, 2017). Pacific Islanders, and Marshallese specifically, are also underrepresented in research, which perpetuates and further obscures these health disparities impacting this vulnerable community (Compact of Free Association Community Advocacy Network, 2014;McGrath & Ka'ili, 2010;Palafox et al, 2002;Roehr, 2010).…”
Section: Introductionmentioning
confidence: 99%